2022
DOI: 10.1136/sextrans-2021-055361
|View full text |Cite
|
Sign up to set email alerts
|

High proportions of rectal and pharyngeal chlamydia and gonorrhoea cases among cisgender men are missed using current CDC screening recommendations

Abstract: ObjectivesPharyngeal and rectal Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections are often undiagnosed due to their asymptomatic nature. This study aims to determine (1) the prevalence of CT/NG infections by anatomical site among cisgender men; (2) the proportion of missed CT/NG rectal/pharyngeal infections if urogenital testing alone was performed or screening depended on self-reported behaviour alone; and (3) the predictive probability of self-reported behaviours for rectal CT/NG.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Over 40% of chlamydia infections that were missed on one swab were identified at the other anatomical site, which ensured prompt identification and treatment of infection for these participants. This recommendation to complete comprehensive testing aligns with literature which has identified similarly high rates of rectal infections among MSM who deny receptive anal sex ranging between 20–35% [ 19 21 ]. Another lesson from this study is that clinicians should consider retesting patients if they obtain negative test results but have a high clinical suspicion of infection (e.g., if the patient is symptomatic or is a contact of someone diagnosed with chlamydia or gonorrhea).…”
Section: Discussionsupporting
confidence: 72%
“…Over 40% of chlamydia infections that were missed on one swab were identified at the other anatomical site, which ensured prompt identification and treatment of infection for these participants. This recommendation to complete comprehensive testing aligns with literature which has identified similarly high rates of rectal infections among MSM who deny receptive anal sex ranging between 20–35% [ 19 21 ]. Another lesson from this study is that clinicians should consider retesting patients if they obtain negative test results but have a high clinical suspicion of infection (e.g., if the patient is symptomatic or is a contact of someone diagnosed with chlamydia or gonorrhea).…”
Section: Discussionsupporting
confidence: 72%
“…In clinical practice, this translates to only screening MSM for rectal CT/GC if they report receptive anal sex (RAS). However, in a recent US study where clinic patients were screened for rectal CT/GC regardless of reported behaviors, 32% of all rectal CT cases and 40% of all rectal GC cases among MSM were among patients who did not report RAS 5 . Furthermore, a number of studies have found that behaviors other than RAS (e.g., rimming, use of sex toys, fingering) may lead to rectal CT/GC acquisition 6–8 .…”
mentioning
confidence: 99%
“…However, in a recent US study where clinic patients were screened for rectal CT/GC regardless of reported behaviors, 32% of all rectal CT cases and 40% of all rectal GC cases among MSM were among patients who did not report RAS. 5 Furthermore, a number of studies have found that behaviors other than RAS (e.g., rimming, use of sex toys, fingering) may lead to rectal CT/GC acquisition. [6][7][8] However, most of these estimates were obtained from populations who also report RAS; thus, it is difficult to determine how common anal exposures are among men who do not engage in RAS and which specific behaviors other than RAS may lead to rectal CT/GC acquisition.…”
mentioning
confidence: 99%
“…Pharyngeal gonorrhea may be more difficult to treat partly because of less good penetration of antibiotics into pharyngeal tissues compared with genital/rectal sites. 4,5 Rectal STI dramatically increases the risk for HIV acquisition for both men and women 6 and therefore warrants more attention and assessment. In studies among men who have sex with men (MSM), extragenital chlamydia and gonorrhea can persist for many months and are likely to serve as a reservoir of infection.…”
mentioning
confidence: 99%
“…Extragenital STIs are often asymptomatic and may go undetected without screening. Pharyngeal gonorrhea may be more difficult to treat partly because of less good penetration of antibiotics into pharyngeal tissues compared with genital/rectal sites 4,5 . Rectal STI dramatically increases the risk for HIV acquisition for both men and women 6 and therefore warrants more attention and assessment.…”
mentioning
confidence: 99%